Exposing paternalistic thinking in the novels Al-Sabbār and Abd al-Shams by Sahar Khalifa - المشهور, أمين; لطفية برهم; زكوان العبدو (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research focuses on the novels "The Cactus" and "Sun Dancers" by Sahar Khalifa, as two parts carrying feminist thought that addresses the reality of women amidst the experience of entering society and its official institutions, and the resulting rejection and superficial acceptance that open up to a rejection of her presence ranging from absence to forced disappearance, which is not the result of an individual, momentary rejection, but rather the result of accumulated intellectual thought contributing to the production of cultural individuals as carbon copies of their paternal ancestors. Thus, the man appears realistically and paper-wise as a normative value that summons paternal thought from absence to presence. Therefore, the author worked on exposing paternal thought and transforming it from a normative hierarchy and centrism to a normative of accountability and revelation that render paternal thought in a state of helplessness, transitioning it from action to reaction, and resulting in the reproduction of binary concepts in both social and cultural thought. The questions the research faces and seeks to answer are: How did the author work on exposing the influence of paternal culture on individuals? Is social rejection of women limited to paternal thought, or are there other factors that contribute to the process of rejection and exclusion on both the manifest and latent levels? Did the author's work in tracing paternal thought extend beyond exposure to refutation and rebellion against it